IMPLIKASI EKONOMI DARI POLA KONSUMSI PANGAN DAN NON PANGAN MASYARAKAT KOTA MATARAM TAHUN 2018 - 2022 - IDA BAGUS EKA ARTIKA; IDA AYU KETUT MARINI (GANEC SWARA, 2023)
The increasing of household income, in general, will tend to change consumption patterns, especially the consumption patterns for food and non-food. According to Engel, in accordance with the research he conducted, it was stated that when income increases, the proportion for food expenditure will decrease, even though in absolute terms the amount increases. A decrease in the proportion of expenditure on food will be followed by an increase in the proportion of expenditure on non-food. This study aims to determine the pattern of consumption of the people of the city of Mataram in terms of consumption of food and non-food and the implications for the economy of the city of Mataram.  The results was found that the higher the level of family income, the tendency for the proportion of expenditure on food to decrease, followed by an increase in the proportion of expenditure on non-food. Likewise, from the household size as reflected by the number of family members, the greater the number of family members, the higher the proportion of expenditure for food consumption, and on the other hand, the proportion for non-food expenditure decreases. From the results of the research, it was suggested to the Mataram City Government to conduct research related to mapping community consumption needs, especially non-food needs, to anticipate the supply of goods and services needed by the community, so that the government can anticipate community needs through more careful economic planning.